Harmoni Keberagaman pada Pemahaman Moderasi Beragama dan Penguatan Nilai-Nilai Kebangsaan di Vihara Siddharta Tangerang - Damana, I Ketut (Abrahamic Religions: Jurnal Studi Agama-Agama, 2023)
The goal of diversity harmony is religious moderation towards national values at the Siddharta monastery. The previous problem was that there were difficulties in building national insights and after being given guidance there was meaning to the values of Pancasila. By conducting this research, it is hoped that after providing an overview of the relationship between Religious Moderation and National Values, there will be an increase in harmony at the Siddharta Tangerang Temple. From the main findings of this research effort, there were previous difficulties for teachers providing an understanding of national values so that the effect of reduced understanding of moderation at the Siddharta Temple. after guidance there is the contribution of the teacher as one of the strengths in the formation of religious moderation. The research method used is descriptive method with a qualitative approach. Data collection through in-depth interactive observations and interviews and findings from research results on religious moderation of strength, courage, honesty and self-esteem. Likewise, these findings provide more understanding of the importance of national values such as; consensus, the 1945 Constitution, and Bhinneka Tunggal Ika. Also efforts of Buddhist values such as; Metta, Karuna, Mudita and Upekkha.AbstrakTujuan harmoni keberagaman pada moderasi beragama terhadap nilai-nilai kebangsaan di Vihara Siddharta. Masalah sebelumnya terdapat kesulitan untuk membangun wawasan kebangsaan dan setelah diberikan bimbingan adanya makna pada nilai Pancasila. Dengan melakukan penelitian ini, diharapkan setelah diberikan gambaran keterkaitan antara Moderasi Beragama dengan Nilai-nilai Kebangsaan terdapat adanya peningkatan harmoni di Vihara Siddharta Tangerang. Upaya-upaya penelitian ini dari temuan utama terdapat sebelumnnya kesulitan guru memberikan pemahaman nilai-nilai kebangsaan sehingga berpengaruh pemahaman moderasi berkurang di Vihara Siddharta. setelah adanya bimbingan terdapat adanya kontribusi guru sebagai salah satu kekuatan terbentuknya moderasi beragama. Metode penelitian yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Pengumpulan data melalui interaktif secara mendalam pengamatan dan wawancara dan temuan dari hasil penelitian pada moderasi beragama adanya kekuatan, keberanian, kejujuran dan harga diri. Begitu juga temuan ini memberikan pemahaman yang lebih pada  pentingnya nilai-nilai kebangsaan seperti; konsensus, UUD 1945, dan Bhinneka Tunggal Ika. Juga upaya-upaya nilai Buddhis seperti; metta, karuna, mudita dan upekha.